Les conditions psychologiques et didactiques du développement de l'activité personnelle des élèves de maternelle au cours des rituels du matin - Marielle Purdy; Maryvonne Merri (Nantes Université, 2015)
This article offers a multidisciplinary review of the functions of school rituals. Firstly, three categories of functions are analyzed: social functions, learning functions, and language functions. In this research, sociological and anthropological references are articulated with Vygotsky's cultural psychology and didactics, revealing the potential functional richness of school rituals. Secondly, in order to analyze this multi-functionality and its implementation, we propose, following Garcion-Vautor, to mobilize the structural approach developed by Rivière.